A new deep-water species of Discias Rathbun, 1902 (Decapoda: Caridea: Disciadidae) from the Gulf of Aqaba, northern Red Sea - Anker, Arthur (Zootaxa, 2023)
A new species of the caridean shrimp genus Discias Rathbun, 1902 is described from the Gulf of Aqaba in the northern Red Sea off the coast of Saudi Arabia. Discias forsskali sp. nov. is unique within the genus Discias, combining the following morphological features: (1) rostrum elongate, triangular, pointed distally, non-lanceolate, with serrations on the lateral margins extending onto the orbital margin; (2) posterodorsal margins of all pleonites smooth, unarmed; (3) mandible with well-developed, biarticulated palp; (4) dactylus of third to fifth pereiopods with row of spinules on ventral margin, dactylus of fifth pereiopod smooth dorsally; (5) uropodal exopod with straight, non-serrated lateral margin; and (6) posterior margin of telson with nine (four pairs + one) spiniform setae. The holotype and single known specimen of the new species, an ovigerous female, was collected by ROV at a depth of 387.4 m.